On the Meaning of on/ant: How Relevant is the Concept of Contact? - Stasiūnaitė, Ieva; Šeškauskienė, Inesa (Kalbotyra, 2004)
The paper sets out to examine the relevance of the concept of ‘contact’ and/or ‘(the top of) the surface’ in the explication of the meaning of on in English and ant in Lithuanian. The investigation of a corpus of English and Lithuanian data revealed that the term is largely superfluous and imprecise, also in many cases a result of interpreting larger strings of context and an outcome of realising the overriding concept of ‘support’, underlying the prototypical meaning of on and ant.